A LOOK AT BRAZIL TODAY: GENDER AND RACE IN THE PRODUCTION OF BRAZILIAN WOMEN WRITERS - Ceneviva Nigro, Claudia Maria [UNESP] (Univ Estado Mato Grosso, 2018)
(Re) thinking Brazil, through representation that makes life more prosaic - as a process of transformation - is embedded in literary language. In view of this particular nature, literature allows (re) thinking constructs of gender and race. In this way, it can be said that poetics of gender studies and subaltern studies can function as an artistic militancy, vehement and biting against the models imposed by current culture. It is a literature without remorse which - embracing political stratagems that promote self-definition and total expression - modifies values and laws, making institutions and relationships oppressive. This article will try to problematize the plurality of meanings that productions of Afro-Brazilian women bring to literature today.
Keywords: Subaltern literature; Afro-Brazilian Literature; Genre